Pathophysiology and Treatments of Oxidative Injury in Ischemic Stroke: Focus on the Phagocytic NADPH Oxidase 2 - Carbone, Federico (Antioxid Redox Signal, 2015)
Significance: Phagocytes play a key role in promoting the oxidative stress after ischemic stroke occurrence. The phagocytic NADPH oxidase (NOX) 2 is a membrane-bound enzyme complex involved in the antimicrobial respiratory burst and free radical production in these cells. Recent Advances: Different oxidants have been shown to induce opposite effects on neuronal homeostasis after a stroke. However, several experimental models support the detrimental effects of NOX activity (especially the phagocytic isoform) on brain recovery after stroke. Therapeutic strategies selectively targeting the neurotoxic ROS and increasing neuroprotective oxidants have recently produced promising results. Critical Issues: NOX2 might promote carotid plaque rupture and stroke occurrence. In addition, NOX2-derived reactive oxygen species (ROS) released by resident and recruited phagocytes enhance cerebral ischemic injury, activating the inflammatory apoptotic pathways. The aim of this review is to update evidence on phagocyte-related oxidative stress, focusing on the role of NOX2 as a potential therapeutic target to reduce ROS-related cerebral injury after stroke. Future Directions: Radical scavenger compounds (such as Ebselen and Edaravone) are under clinical investigation as a therapeutic approach against stroke. On the other hand, NOX inhibition might represent a promising strategy to prevent the stroke-related injury. Although selective NOX inhibitors are not yet available, nonselective compounds (such as apocynin and fasudil) provided encouraging results in preclinical studies. Whereas additional studies are needed to better evaluate this therapeutic potential in human beings, the development of specific NOX inhibitors (such as monoclonal antibodies, small-molecule inhibitors, or aptamers) might further improve brain recovery after stroke. Antioxid. Redox Signal. 23, 460–489.